Pengaruh Variety Seeking, Brand Image Dan Product Quality Terhadap Keputusan Pembelian (Studi Kasus Pada Konsumen Produk Skincare Ms Glow Sumbawa) - Lyla Anattasya Saputri; Afi Rachmat Slamet; Mohammad Rizal (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This study aims to analyze, describe and determine the effect of variety seeking, brand image, product quality on purchasing decisions (a case study on skincare product consumers Ms Glow Sumbawa). This type of research uses purposive sampling using a quantitative approach and data collection techniques used in this study are primery as the analysis technique. In this study the sample used is 85 respondents who will be the object of research. The method used is by using the test of validity, reliability, normality, multicollinearity test, heteroscedasticity test, multiple linear regression analysis test, f test, t test and coefficient of determination using SPSS. The results of this study indicate that variety seeking has no significant effect on purchasing decisions on MS Glow skincare products, while brand image and product quality show that brand image and product quality have a significant positive effect on purchasing decisions on MS Glow skincare products.Keywords : variety seeking, brand image, product quality, purchasing decisions